2013
DOI: 10.1016/j.msea.2013.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of uni-axial and bi-axial deformation behavior of pure Titanium after hydrostatic extrusion

Abstract: Titanium Hydrostatic extrusion Texture Uni-axial deformation behavior Bi-axial deformation behavior Anisotropy Coarse-grained commercially pure (CP) Titanium is subjected to hydrostatic extrusion resulting in the formation of ultrafine lamellar-type microstructure having very strong fiber texture. Uni-axial tensile tests of longitudinal and transverse specimens are carried out to study anisotropy of uni-axial deformation behavior of hydrostatically extruded CP Titanium. Small punch testing of longitudinal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…This result is in contrast with the previously reported for Ti deformed by compression or cold rolling where saturation of the positron annihilation parameters was observed for thickness reduction between 10 and 15%, which corresponds to true deformation from 1.9 to 2.3, respectively . Under the present conditions, hydrostatic extrusion is accompanied by a significant adiabatic heating, which results in a estimated temperature increase in the range of 240–400 °C . Initial recovery stages of deformed and irradiated Ti have been observed on this temperature range, and in consequence the effect of dynamic recovery during the hydrostatic extrusion process will reduce the density of points defects that act as effective positron traps so that trapping saturation is not attained for a true deformation as large as ϵ = 3.24.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This result is in contrast with the previously reported for Ti deformed by compression or cold rolling where saturation of the positron annihilation parameters was observed for thickness reduction between 10 and 15%, which corresponds to true deformation from 1.9 to 2.3, respectively . Under the present conditions, hydrostatic extrusion is accompanied by a significant adiabatic heating, which results in a estimated temperature increase in the range of 240–400 °C . Initial recovery stages of deformed and irradiated Ti have been observed on this temperature range, and in consequence the effect of dynamic recovery during the hydrostatic extrusion process will reduce the density of points defects that act as effective positron traps so that trapping saturation is not attained for a true deformation as large as ϵ = 3.24.…”
Section: Discussionmentioning
confidence: 83%
“…The analyses were carried out in a TECNAI 20‐FEG microscope operated at 200 kV and equipped with an X‐ray energy dispersive spectrometer (EDX), and a scanning transmission electron microscope (STEM) modulus with a dark‐field high‐angle annular detector (HAADF) for Z‐contrast. A description of the microstructure and mechanical properties of hydrostatic‐extruded CP Ti under experimental conditions equivalent to the conditions described in this work have been previously published by Moreno‐Valle et al The main results were the formation of an ultrafine lamellar‐type microstructure for large area reductions and an increase of the mechanical strength at the expense of the material ductility …”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is clearly seen in the work-hardening graph illustrated in Figure 3 and can be attributed to the anisotropy of defect density, crystallographic orientation, and grain size distribution. The effect of the anisotropy after HE was investigated in detail in the previous work of the authors [36] and by Moreno-Valle et al [38] The values of Young's modulus determined by tensile tests are summarized in Table IV. It was revealed that HE processing of TNZ leads to a decrease in Young's modulus from 78.2 for initial to 73.2 GPa for HE20 then to 69.6 GPa for the HE16 sample.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of deformation parameters on the flow behavior including flow stress, strain rate sensitivity exponent ( m ), strain hardening exponent ( n ), and apparent activation energy for deformation ( Q ) was studied to understand the hot workability of titanium alloys . The m and n ‐values characterize some deformation mechanisms and depend on the microstructure evolution largely .…”
Section: Introductionmentioning
confidence: 99%